Long‐term follow‐up of biliary complications after adult right‐lobe living donor liver transplantation. (10th April 2015) - Kim, Peter T.W.; Marquez, Max; Jung, James; Cavallucci, David; Renner, Eberhard L.; Cattral, Mark; Greig, Paul D.; McGilvray, Ian D.; Selzner, Markus; Ghanekar, Anand; Grant, David R.
Abstract Introduction Long‐term biliary complications after living donor liver transplantation (LDLT) are not well described in the literature. This study was undertaken to determine the long‐term impact of biliary complications after adult right‐lobe LDLT. Methods This retrospective review analyzed an 11‐yr experience of 344 consecutive right‐lobe LDLTs with at least two yr of follow‐up. Results Biliary leaks occurred in 50 patients (14.5%), and strictures occurred in 67 patients (19.5%). Cumulative biliary complication rates at 1, 2, 5, and 10 yr were 29%, 32%, 36%, and 37%, respectively. Most early biliary leaks were treated with surgical drainage (N = 29, 62%). Most biliary strictures were treated first with endoscopic retrograde cholangiography (42%). There was no association between biliary strictures and the number of ducts (hazard ratio [HR] 1.017 [0.65–1.592], p = 0.94), but freedom from biliary stricture was associated with a more recent era (2006–2010) (HR 0.457 [0.247–0.845], p = 0.01). Long‐term graft survival did not differ between those who had or did not have biliary complications (66% vs. 67% at 10 yr). Conclusions Biliary strictures are common after LDLT but may decline with a center's experience. With careful follow‐up, they can be successfully treated, with excellent long‐term graft survival rates.